The Nuclear Submarine Scales in Gibraltar and Rota, and the Radiological Emergency Plans - Luis Romero Bartumeus (Cuadernos de Gibraltar, 2021)
When a British or North American nuclear-powered submarine docks at the southern dock of the port / naval Base of Gibraltar, it is usual for environmental groups in the neighbouring Spanish area to come to the fore protesting this scale and airing the dangers it entails that repeated presence. Regardless of the numbers and given the repetition of these visits, it is worth considering what is the relevance of the Gibraltar facilities, and also those of Rota, for the operation of these platforms and. Moreover, it is key to stress the importance of the submarines – nuclear or not – for the Navies of the countries that possess them, in the context of the current international strategic situation. This article evaluate what happened and what was done when in Gibraltar a submarine of the Royal Navy, the ‘HMS Tireless’, was docked for a year repairing a failure in the primary cooling circuit of its nuclear reactor. The security aspect of the population living a very short distance from the nuclear submarine berths is reflected in the nuclear emergency plan available to Gibraltar and the absence of it on the Spanish side of the Gate. The article will also review the internal nuclear emergency plan available to the US-Spain Rota Base and the absence, once again, of a civil emergency plan for the towns that surround it.